HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA KELAS XI IPA SMA NEGERI 1 CERENTI KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Rendy, Rendy Rendy Rendy; Juwita, Ardiah Juwita Ardiah; ', Yuherdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT : The results of the identification problems indicate that one factor affecting the long jump squat style is less than the maximum force is the lack of leg muscle explosive power. This study aimed to find out how much leg muscle explosive power affect the long jump ability students of class XI Science SMAN 1 Cerenti Regency Cerenti District of Kuantan Singingi.This research is correlational research with populations in class XI Science SMAN 1 Cerenti Regency Cerenti District of Kuantan Singingi. Sampling technique in this study by using total sampling where the entire population sampled, thus the number of samples in this study was 26. From the analysis of the data shows that there is a significant correlation between the variables x and y variables. based on the results of this study concluded that there is a significant corelation between leg muscle explosive power with the ability to long jump squat style, where the level of Î± = 0.05 level = 4.21 The obtained t count> t table = 2.06 so that Ho is rejected and Ha accepted. The correlation of variable X to variable Y being categorized and 0.425 count obtained r> r table = 0.388. Keywords: explosive leg muscle power, long jump style squat style